Analisis Dampak Orang Tua Strict Parents dalam Cerpen “Gadis” Karya Hening Apriliananda Wikunurani Menggunakan Pendekatan Mimetik - Bagus Febriana Rahmawan; Syahril Ramadan; Saproji Saproji (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This research focuses on analyzing the impact of strict parents in the short story "Gadis" by Hening Apriliananda Wikuruni using a mimetic approach. The research method used is descriptive qualitative. The resource used is the short story "Gadis" by Hening Apriliananda Wikuruni. The data collection technique used was to read critically and carefully the entire story content of the short story. The analysis technique is to examine the impact of the strict parents in the short story, then compare it with real life reality. The results of this research are that the short story describes an authoritarian parenting pattern, then this parenting pattern creates violence in the family which results in the girl (the main character of the short story) experiencing mental disorders. The girl tried to commit suicide twice but ultimately failed. In real life, we encounter this a lot and it is not something new. The impact that often occurs in real life is that children have difficulty making decisions, there is tension between parents and children, and the child has the potential to commit criminal acts.